MUSEUM BIOGRAFI ANAK AGUNG PANDJI TISNA DI LOVINA, BULELENG DAN POTENSINYA SEBAGAI PUSAT PELESTARIAN KARYA SASTRA DI BALI UTARA - Gede Narayasa Utama (ACARYA PUSTAKA, 2025)
The Anak Agung Pandji Tisna Biography Museum is a museum that displays collections related to the life journey of Anak Agung Pandji Tisna with a building built with traditional Balinese carvings. The aims of this research are; (1) To find out the background to the establishment of the Agung Pandji Tisna Children's Biography Museum, (2) To find out about the collection of the Agung Pandji Tisna Children's Biography Museum which has the potential to become a center for preserving literary works in North Bali. The research method used is qualitative research through a collection process using interviews, observation and document study methods. The results of the research show that the Anak Agung Pandji Tisna Biography Museum was founded by Anak Agung Ngurah Brawida as a form of respect for the literary figures of the new generation of poets and as the initiator of the tourist destination and the name "Lovina". The Agung Pandji Tisna Children's Biography Museum has a collection of 1,986, consisting of print collections and artifacts. The print collection it owns presents a variety of literary works, so the collection can be used as a source of literary information. However, there are several obstacles faced in maximizing its potential as a center for the preservation of literary works, including the lack of competent human resources, limited funds to manage the museum, lack of encouragement or assistance from the government, lack of promotion by the museum to introduce its existence, and the building. narrow and less strategic.